Critical Discourse Analysis of the News Subject-Related to Beatings: A Case of Lampost.co Webpage - Amalia Sabilla Mukhtar (Bulletin of Social Studies and Community Development, 2023)
Abstract: This paper will present how the author critically analyzes the cases of beatings that occurred in Lampung province which were published by official and trusted news websites, namely Lampost.co owned by the Lampung post media. The author chooses news from this media because it has been registered with the press council which oversees the official press media in Indonesia, so that the validity and accountability of the news published is very reliable, in contrast to news published on private websites or blogspots managed by individuals. , it could be that the news written for the purpose of Jah is for the benefit of the individual himself or only certain groups. The author here is discourse analysis on the news. The method used by the author is descriptive qualitative, namely the presentation of the results of the analysis in this article is based on the data contained in the news. The data found is in the form of structure, superstructure, microstructure, then the existing macrostructure. on the news of the beating. The author also conducts critical discourse analysis textually, namely related to the news explaining what, how the description, interpretation and explanation of the news is about. The data source is the beating news on the Lampost.co page. The result is that elements of the setting are found in the news, namely Labuhan Maringgai. The setting is the backdrop for the beatings of victims as well as the arrest of perpetrators. Journalists use a deductive pattern to present news content, beginning with public opinion, followed by supporting sentences.     Keywords: discourse analysis, news of beatings, lamppost